Effects of TEACCH on social functioning in individuals with autism spectrum disorders: a systematic review and meta-analysis - Shanshan Shi; Shuang Song; Huitong Wang; Pengfei Li; Xiaoying Zhang (BMC Pediatrics)
Abstract Objective To investigate the effects of Treatment and Education of Autistic and Related Communication Handicapped Children (TEACCH) on social functioning in individuals with autism spectrum disorders (ASD). Methods Relevant studies on TEACCH intervention in ASD individuals were systematically searched in PubMed, The Cochrane Library, Embase, CNKI, and Wanfang from inception to March 2024. The main outcome measures were social, cognitive performance, fine motor, communication, daily living, imitation, and cognitive verbal skills. Data were meta-analyzed using R studio (4.1.2). Results Eleven studies involving 701 ASD individuals were included in this study. The TEACCH group had significantly higher socialization score [MD = 0.6, 95% CI(0.2, 1.0)], Cognitive Performance Scale score [MD = 1.34, 95% CI(0.09, 2.58)], and fine motor score [MD = 0.7, 95% CI(0.4, 1.0)] but significantly lower Autism Behavior Checklist score [MD = -1.57, 95% CI(-2.11, -1.02)], Childhood Autism Rating Scale score [MD= -0.7, 95%CI(-1.0, -0.3)], and Autism Treatment Evaluation Checklist score [MD= -0.7, 95% CI(-1.0, -0.3)] compared to the control group. There were no significant differences in other outcome measures. Conclusion TEACCH is a promising intervention for improving the social skills, cognitive performance, and fine motor functions of ASD individuals. However, further studies are warranted to confirm the effectiveness of TEACCH on ASD core symptoms.